Lies my teacher told me : everything your American history textbook got wrong - Loewen, James W. (New York : Simon & Schuster, 2007)
Criticizes the way history is presented in current textbooks, and suggests a fresh and more accurate approach to teaching American history.
Originally published: New York : New Press,1995.
"A Touchstone book."
Includes bibliographical references (p. [363]-434) and index.
Keywords: United States -- History -- Textbooks; United States -- Historiography; Indians of North America in textbooks; Thanksgiving Day in textbooks